Institutionalizing Global Governance in the Sphere of Security and Defense: The European Context - Anatoliy KALYAYEV; Irina SURINA; Lesia RUDENKO (Communications of International Proceedings, 2020)
The process of transformation of European institutions in the field of security and defense is surveyed in the context of ensuring their institutional sustainability in the view of new geopolitical challenges and threats. The institutional system of governance in the sphere of EU security is scrutinized on the base of a systematic approach. The formation processes of a modern system of collective security and defense in Europe are researched in their dialectical connection as to ensure effective cooperation of institutions. The positions in the capability assessments of the institutions of governance of the European security system and the prospects for improving their effectiveness are generalized, in particular, within NATO in conditions of current conflicts. The deepening of integration in the provision of collective protection is being updated due to the need to expand the powers of the EU's supranational institutions on security and defense and in order to mobilize efforts to counteract global threats. Emphasis is placed on rethinking the European Union's ability to countervail threats related to gaining strategic autonomy. The justification is based on the conclusion that in order to ensure the institutional sustainability of the EU supranational security structures it is expedient to unite the military-strategic plans of all EU defense institutions of different levels and to ensure their compatibility with NATO structures on the basis of centralized management (Joint Command), the decisions of which must be mandatory to perform by all countries included in the system of collective security and defense. The measure of  national sovereignty limitation, in this context, must correlate with the scale of threats and be adjusted in conditions of real military-political situation. It is concluded that a joint integrated system for monitoring the identification of threats and the effectiveness of existing management structures in the field of security and defense is able to optimize all defense institutions on the basis of crisis management and counteracting hybrid threats on an ongoing basis.
Keywords: European Security Governance; Institutional Sustainability; Collective Defense; Geopolitical Threats